Simulation study on reinforced concrete beam with variation of shape and size of opening - Kun, Chee Yong (2017)
Provision of opening will affect the ductility and rigidity of the RC beam due to stress concentration around the opening. The effect of provision of opening in normal RC beam was significance due to its limited height. In this study, 8 samples of rectangular RC beam with different shape and size of opening were analysed using FEM. One solid beam (Beam S1) was used as control sample, RC beam with square opening (Beam S2), circular opening (Beam S3), rectangular opening (Beam S4) and beam with two circular opening (Beam S5). Another 3 sample were different from size of opening with 60mm x 40mm, 100mm x 48mm and 100mm x 80mm which is Beam S6, Beam S7 and Beam S8 respectively. The FEM software used to run the analysis is ANSYS 12.0 software. All of the sample were tested under four-point loading. The load apply to all the sample were the same. The effect of opening with different shape and size were studied in term of mid-span deflection and crack pattern. From the test results, it can be concluded that, the circular opening is the best shape of opening as it give least mid-span deflection compare to other geometries of opening. Due to orthogonal corner of rectangular opening, crack concentrate at the corner causing early cracking to occur. When opening was provided, it cause stress concentration around the opening. Crack pattern become more serious and obvious when opening size increase.